THE EMPLOYMENT OF THE TECHNOLOGICAL INNOVATIONS IN THE EDUCATIONAL PROCESS - ABDEL, AMAL; AHMAD, FATTAH (Sriwijaya University Learning and Education International Conference, 2016)
Teachers are the cornerstone in the educational process. Employing the technological innovations doesnot mean minimizing the importance of the teacherâs role as some may imagine. The employment oftechnology in the educational process is considered one of the most important and contemporarytopics. The aim of this paper is to develop skills of the employment of technological innovations forpreparatory stage teachers. This research contributes to the effective employment of the technologicalinnovations in the preparation and explanation of the educational lessons. Teachersâ correct usage ofthe technological innovations will enhance the process of education. Besides, the development of theskills of employment of technological innovations of teachers may overcome difficulties that facepreparatory stage teachers in dealing with technological innovations in the educational process.Finally, it provides a training program of the skills of employment of technological innovations ofteachers.